Effect of proton pump inhibitors on dental implants: A systematic review and meta-analysis - Dileep Nag Vinnakota; Rekhalakshmi Kamatham (Wolters Kluwer Medknow Publications, 2020)
Aim: The present systematic review aims to determine the evidence on the impact of proton pump inhibitors (PPIs) on dental implants. Settings and Design: This secondary qualitative and quantitative research was done using a pre-specified question and inclusion criteria. Materials and Methods: A systematic search was conducted in electronic databases such as PubMed, Ovid, and Cochrane. All the studies that assessed the effect of PPIs on dental implants were included, irrespective of the design. Literature review, letter to editors, short commentaries, and opinion articles were excluded. Results and Statistical Analysis Used: A total of three publications fulfilled the inclusion criteria. All these included articles were retrospective cohort studies; the methodological quality was assessed using Newcastle-Ottawa scale. A total of 452 implants were placed in 149 PPI users, whereas 6798 were positioned in 2241 nonusers. Of these, 43 and 212 implants failed in users and nonusers, respectively (odds ratio: 2.91, 95% confidence interval: 2.06-4.11). The meta-analysis was performed using the statistical software Review Manager, and a fixed-effect model was used to obtain the odds ratio. The success rate of implants based on age, gender, smoking, and bone augmentation could be combined only from two studies, which revealed a considerable effect of these factors. Conclusion: As far as the available evidence is considered, it seems as if the usage of PPI has a detrimental effect on the success of dental implants. This influence needs justification as none of the included studies segregated the data based on confounding factors. Hence, there is a need to conduct well-designed, prospective, randomized clinical trials with balanced confounding factors to derive a proper conclusion.